The existential needs of the elderly: the problem of quality of Life - Abdina, A.K.; Ibzharova, Sh.A.; Kakimzhanova, M.K. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
Consideration of such an essential and significant part of the problem of population ageing as their existential needs since it is at this age that a person is profoundly confronted with life-meaning experiences. The paper uses comparative research methods and conceptual and hermeneutic analysis of philosophical texts. The existential needs of a person in old age directly affect the quality of his life, awareness of himself as a creative person, freedom in his manifestations, responsible for his actions, and living in harmony with himself and society. The search for roots and identity complements a person's holistic worldview, making him the creator of his own life, and not a shadow of the years he has lived. Unrealized or unsatisfied existential needs destroy the integrity of a person, negatively affecting the quality of his life. The problem of population ageing is closely connected not only with economic, demographic and social problems, but it also expresses, first of all, the existential essence of a person, measured by the quality of his life. The quality of life of older people would be significantly higher if existential needs were consciously satisfied.
Егде жастағы адамдардың экзистенциалды қажеттіліктері: өмір сапасы мәселесі
Экзистенциальные потребности пожилых людей: проблема качества жизни
Keywords: population ageing; elderly people; quality of life; existential needs; existential experiences; active longevity